Transformasi Model Kelas Virtual Nusantara dengan Spatial.io sebagai Upaya Meningkatkan Multiskill Mahasiswa PPG IPS di Era Society 5.0 - Purwanto, Purwanto; Hudiyanto, R. Reza; Sukriono, Didik; Maulana Yusuf, Alfariz; Eka Israni, Mayang; Asyarifah, Runing Fikriyah; Rizkyanto, Muhammad Yusuf (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The transformation of education in the era of Society 5.0 demands the integration of the latest technology to create effective and relevant learning. Especially for a professional teacher as a learning innovator who should have multiple skills.  In the destructive era, a fundamental change needs to be made by professional teachers. This research aims to develop a Spatial.io-based virtual classroom model to improve the multiskills of Teacher Professional Programme (PPG) students through a systematic approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Spatial.io, as a three-dimensional (3D) space-based immersive platform, is designed to support collaborative interaction, creative exploration, critical thinking, and experiential learning, which are key in equipping students with communication, technology, and problem-solving skills. The dynamics of physical, social, and cultural geography diversity necessitate a collaborative classroom that can facilitate prospective social studies teachers to study together by bringing out the characteristics of their respective environments. This study involved the development and implementation of the Spatial.io virtual classroom prototype which was tested on PPG students in various regions of the archipelago. The results showed that the integration of the ADDIE model in the development of this virtual classroom ensured a learning design that was responsive to student's needs and the local context. The evaluation phase showed significant improvements in learning engagement, collaborative ability, and multiskill mastery, compared to traditional online learning methods. The Spatial.io-based virtual classroom model designed through the ADDIE approach provides an innovative solution in supporting educational transformation in the digital era. This study suggests wider implementation and customization for various learning contexts, to create a competent, adaptive, and globally ready workforce.